Prognostic factors in children and adolescents with differentiated thyroid cancer treated with total thyroidectomy and radioiodine therapy: a retrospective two-center study from China - Wang, Congcong; Li, Yutian; Wang, Guoqiang; Liu, Xinfeng; Zhang, Yingying; Lu, Chenghui; Li, Jiao; Han, Na; Wang, Zenghua; Si, Zengmei; Li, Fengqi; Lu, Gaixia; et al. (Frontiers in Endocrinology, 2024)
Purpose This two-center study aimed to explore the main prognostic factors affecting the final disease status in children and adolescents with differentiated thyroid cancer (caDTC) following total thyroidectomy and radioiodine therapy (RAIT). Materials and methods All caDTC patients from two centers in the period from 2004-2022 were retrospectively included. At the last follow-up, the patients’ disease status was assessed and classified as an incomplete response (IR) or as an excellent or indeterminate response (EIDR). Then, the difference in preablation stimulated thyroglobulin (ps-Tg) levels between the two groups was compared, and the threshold for predicting IR was determined using receiver operating characteristic (ROC) analysis. Moreover, univariate and multivariate analyses were conducted to identify the factors influencing the patients’ ultimate disease outcomes. Results A total of 143 patients (98 females, 45 males; median age 16 years) were recruited. After a median follow-up of 42.9 months, 80 patients (55.9%) exhibited an EIDR, whereas 63 patients (44.1%) exhibited an IR. Patients with an IR had significantly greater ps-Tg levels than did those with an EIDR (median ps-Tg 79.2 ng/mL vs. 9.3 ng/mL, p<0.001). The ROC curve showed that ps-Tg ≥20 ng/mL was the most accurate for predicting IR at the last follow-up. According to multivariate analysis, only ps-Tg, T stage and the therapeutic response to initial RAIT were significantly associated with IR. Conclusion In caDTC patients, the ps-Tg level, T stage, and response to initial RAIT are critical final outcome indicators.